Development of Combinatorial Pulsed Laser Deposition for Expedited Device Optimization in CdTe/CdS Thin-Film Solar Cells - Ali Kadhim; Paul Harrison; Jake Meeth; Alaa Al-Mebir; Guanggen Zeng; Judy Wu (International Journal of Optics)
A combinatorial pulsed laser deposition system was developed by integrating a computer controlled scanning sample stage in order to rapidly screen processing conditions relevant to CdTe/CdS thin-film solar cells. Using this system, the thickness of the CdTe absorber layer is varied across a single sample from 1.5 μm to 0.75 μm. The effects of thickness on CdTe grain morphology, crystal orientation, and cell efficiency were investigated with respect to different postprocessing conditions. It is shown that the thinner CdTe layer of 0.75 μm obtained the best power conversion efficiency up to 5.3%. The results of this work shows the importance that CdTe grain size/morphology relative to CdTe thickness has on device performance and quantitatively exhibits what those values should be to obtain efficient thin-film CdTe/CdS solar cells fabricated with pulsed laser deposition. Further development of this combinatorial approach could enable high-throughput exploration and optimization of CdTe/CdS solar cells.